Plasticity in Limbic Regions at Early Time Points in Experimental Models of Tinnitus - Kapolowicz, Michelle R.; Thompson, Lucien T. (Frontiers in Systems Neuroscience, 2020)
Tinnitus is one of the most prevalent auditory disorders worldwide, manifesting in both chronic and acute forms. The pathology of tinnitus has been mechanistically linked to induction of harmful neural plasticity stemming from traumatic noise exposure, exposure to ototoxic medications, input deprivation from age-related hearing loss, and in response to injuries or disorders damaging the conductive apparatus of the ears, the cochlear hair cells, the ganglionic cells of the VIIIth cranial nerve, or neurons of the classical auditory pathway which link the cochlear nuclei through the inferior colliculi and medial geniculate nuclei to auditory cortices. Research attempting to more specifically characterize the neural plasticity occurring in tinnitus have used a wide range of techniques, experimental paradigms, and sampled at different windows of time to reach different conclusions about why and which specific brain regions are crucial in the induction or ongoing maintenance of tinnitus-related plasticity. Despite differences in experimental methodologies, evidence reveals similar findings which strongly suggest that immediate and prolonged activation of non-classical auditory structures (i.e., amygdala, hippocampus, and cingulate cortex) may contribute to the initiation and development of tinnitus in addition to the ongoing maintenance of this devastating condition. The overarching focus of this review, therefore, is to highlight findings from the field supporting the hypothesis that abnormal early activation of non-classical sensory limbic regions are involved in tinnitus induction, with activation of these regions continuing to occur at different temporal stages. Since initial/early stages of tinnitus are difficult to control and to quantify in human clinical populations, a number of different animal paradigms have been developed and assessed in experimental investigations. Traumatic-noise exposure and ototoxic doses of sodium salicylate, the most prevalently utilized animal models to induce experimental tinnitus, are reviewed here. Linking the results observed from these paradigms can be informative in developing more targeted treatment approaches to reduce or to eliminate tinnitus from the human condition.